63.2k views
0 votes
4x squared - 35 y squared ​

4x squared - 35 y squared ​-example-1
User Tartar
by
4.9k points

2 Answers

1 vote

Answer:


= 1)(2x - 5y {)} * (2x + 5y)

Explanation:


1) {4x}^(2) - 25 {y}^(2)


= {2}^(2) {x}^(2) - 25 {y}^(2)


= {2}^(2) {x}^(2) - {5}^(2) {y}^(2)


= (2 {x)}^(2) - {5}^(2) {y}^(2)


= ( {2x)}^(2) - (5 {y)}^(2)


= (2x - 5y) * (2x + 5y)


2)4x^(2) - 35 {y}^(2)


= {2}^(2) {x}^(2) - 5y * 7 {y}


=(2x {)}^(2) - (5y * 7y)

User Lucas Renan
by
4.9k points
2 votes

Answer:

it was helpful to you ✌︎✌︎✌︎✌︎✌︎✌︎✌︎➪♧︎︎︎


4 {x}^(2) - 25 {y}^(2) \\ (2 x) {}^(2) - {(5y)}^(2) \\ (2x + 5y)(2x - 5y)

User Peter T Bosse II
by
5.4k points